DAMPAK KOMPETENSI KEPRIBADIAN GURU PENDIDIKAN AGAMA ISLAM TERHADAP SELF REGULATED LEARNING SISWA - Riany, Helifsia; Muslimah, Muslimah; Khalfiah, Yuliani (TA'LIMUNA: Jurnal Pendidikan Islam, 2023)
This study aims to describe the personality competencies of PAI teachers at SMA PGRI 2 Sampit, Kotawaringin Timur district. In addition, to describe the impact of personality competence of PAI teachers on self-regulated learning of students at SMA PGRI 2 Sampit, East Kotawaringin district. This research method uses qualitative which produces descriptive data to understand a phenomenon naturally. The results of the study are that the personality competencies of PAI teachers at SMA PGRI 2 Sampit are in accordance with personality competency indicators, including a solid and stable personality, mature personality, wise and wise, authoritative and have noble character, PAI teachers have carried it out well. Then the impact of the personality competence of the PAI teacher on students' self-regulated learning is that students can control their behavior in learning, have the independence to determine and assess the learning strategies needed, be disciplined, be responsible. In addition, students' motivation and enthusiasm increased and students did not feel bored and reluctant to participate in learning activities.